EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI, PEMANFAATAN TEKNOLOGI, KEMUDAHAN DAN KOMPETENSI SUMBER DAYA MANUSIA PADA KINERJA KARYAWAN PT BANK MUAMALAT KOTA MEDAN - Khairiyahtussolihah, Assa’adatul; Lisa, Hanna May; Siregar, Indah Permatasari (Journal Of Sharia Banking, 2023)
This research aims to determine the effect of the effectiveness of the application of accounting information systems, technology utilization, ease and competence of human resources on employee performance at PT Bank Muamalat Kota Medan. The respondents in this study were employees of Bank Muamalat in Medan. The number of respondents in this study amounted to 57 respondents from 65 questionnaires distributed. The results of research,Meanwhile, the effectiveness of the application of accounting information systems and the use of technology have an effect but not significantly on the performance of the employees of PT Bank Muamalat Kota Medan.